Inadequate vocal hygiene habits associated with the presence of self-reported voice symptoms in telemarketers. (3rd July 2019) - Fuentes-López, Eduardo; Fuente, Adrian; Contreras, Karem V.
Abstract: Aim: The aim of this study is to determine possible associations between vocal hygiene habits and self-reported vocal symptoms in telemarketers. Patients and methods: A cross-sectional study that included 79 operators from call centres in Chile was carried out. Their vocal hygiene habits and self-reported symptoms were investigated using a validated and reliable questionnaire created for the purposes of this study. Results: Forty-five percent of telemarketers reported having one or more vocal symptoms. Among them, 16.46% reported that their voices tense up when talking and 10.13% needed to clear their throat to make their voices clearer. Five percent mentioned that they always talk without taking a break and 40.51% reported using their voices in noisy environments. The number of working hours per day and inadequate vocal hygiene habits were associated with the presence of self-reported symptoms. Additionally, an interaction between the use of the voice in noisy environments and not taking breaks during the day was observed. Finally, the frequency of inadequate vocal hygiene habits was associated with the number of symptoms reported. Conclusions: Using the voice in noisy environments and talking without taking breaks were both associated with the presence of specific vocal symptoms. This study provides some evidence about the interaction between these two inadequate vocal hygiene habits that potentiates vocal symptoms.